KUALITAS PELAYANAN PERAWAT DI RUANG MEDIKAL BEDAH RUMAH SAKIT SANTA ELISABETH MEDAN - Pomarida Simbolon; Samfriati Sinurat (Nursing Arts, 2021)
The hospital is a health facility that can provide health services to the community and is very important in the process of improvement. Health services which are the main part in hospitals and health units. With good service, hospitals are expected to have competitive advantage with quality and efficient services. A good nurse performance is a guarantee of the quality of health services provided to both sick and healthy patients. In improving the quality of health services improving nurse performance must be high. This study aims to determine the quality of nurses' services in the surgical medical room at the Santa Elisabeth Hospital Medan in 2020. This researcher uses a descriptive study design which is the result of a questionnaire sheet. The population in the study was all nurses in the surgical medical room of the Santa Elisabeth Hospital in Medan with a sample of 30 people. The sampling technique uses total sampling. Respondents can provide a response to the quality of nurse care in the medical room of the Santa Elisabeth Hospital on five dimensions, namely Tangibility, Reliability, Responsiveness, Assurance, and Emphaty. The results of this study indicate that the quality of nurse services from five dimensions shows the majority of nurses have a good responsiveness of 30 people (100%), good Assurance of 30 people (100%), Emphaty for 30 people (100%), good Tangibility of 29 people ( 96.7%), and Reliability as many as 29 people (96.7%). So that researchers can conclude that the quality of nursing services in the medical room of the Santa Elisabet Hospital in Medan in 2020 is good. It is expected that nurses are able to maintain or improve the quality of nurse services well